المواجهة الجنائية للجرائم المرتكبة في الفضاء الخارجي: دراسة مقارنة - عبدالمحسن، محمد عبدالرحمن (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2024)
يعد هذا البحث من الأبحاث التي تهتم بالفضاء الخارجي خاصة مع حداثة القانون حيث نشأ القانون كغيره من القوانين حين وصل الإنسان للفضاء وأصبح ملحا صدور قانون ينظم الفضاء الخارجي، حيث صدرت قرارات الأمم المتحدة بتنظيم أعمال الفضاء الخارجي من اعتداد اتفاقية المبادئ التي تحكم الدول في استكشاف الفضاء وتنظيم كافة الإشكاليات القانونية التي تحكم ذلك وخاصة الجرائم المرتكبة في الفضاء الخارجي. وكان من أبرز نتائج البحث: زيادة انتشار جرائم الفضاء الخارجي. وأن أغلب الدول لا تدخل في اختصاص سيادة الدولة. وأن هناك حلولا تشريعية وعمليه يمكـن مـن خلالها مواجهة جرائم الفضاء الخارجي. وأهم التوصيات: ضرورة التصديق على الاتفاقيات الدولية المتعددة الأطراف التي تنشئ آليات قضائية الجنائية لمحاكمة الطرف الثالث في الجرائم المرتكبة في الفضاء الخارجي. وتعزيز التطور الدائم ومواكبة التشريعات لكشف عن الجرائم قبل وقعها من خلال آليات استخدام الذكاء الاصطناعي في الكشف عن الجرائم الفضائية. وإعادة النظر في المنظومة الجنائية المتعلقة بالجرائم والعقوبات أعمالا لمبدأ الشرعية الجنائية. وإنشاء دوائر ومحاكم متخصصة تكون مهمتها المحاكمات الجنائية على كل ما يهدد الفضاء الخارجي من استعمال الغازات السامة أو يعد خروج على قانون الفضاء الخارجي وكذلك الاتفاقيات الدولية المنظمة لهذا الشأن. This research is considered one of the researches that is concerned with outer space, especially with the modernity of outer space law, as outer space law arose like other laws when man arrived in space and it became urgent to issue a law concerned with outer space, as the United Nations resolutions regulating the activities of outer space were prepared by the Convention on the Principles Governing Countries in outer space exploration. It was out of the results of the research: the increase in the spread of outer space crimes. Most countries not intervened in the jurisdiction of the State's sovereignty. And that there are legislative solutions and practice through which the ounces of external spaces could be faced. The most important recommendations: the need to ratify the multilateral international conventions that fainen criminal judicial proceedings to try the third party in crimes committed in outer space. Promoting permanent development and keeping legislation to detect crimes before signed by using artificial intelligence in detecting space offices. Recognizing the criminal and criminal system of the criminal legal principle of the Chamber of Criminal Characterism and the specialized courts and their specialized trials are of all criminal omiots to thus that use orxicity of the ounces of hazardous oil and the international conventions of the international community.
Keywords: الفضاء الخارجي -- القانون الجنائي -- الاتفاقيات الدولية -- الأمم المتحدة